Authority Figures (The Hastings Center report, 2012)
“Authority Figures”: letters from Robert M. Veatch and Richard W. Clark about “What Health Care Providers Know” (September-October 2011), with a reply from Daniel Groll; “Research Is Care”: a letter from Nancy M.P. King about “Can Research and Care Be Ethically Integrated?” (July-Aug 2011); “An Unintended Misrepresentation”: a letter from Sharmila Dissanaike about “Too Much to Ask?” (July-Aug 2011), with a reply from Patricia Lyndale and Lauren Smith; “Toward Universal Standards”: a letter from John E. Jesus about “Questioning the Universality of Medical Ethics: Dilemmas Raised Performing Surgery around the Globe” (September-October 2011); and “Uncomfortable Humor”: a letter from Tom Tomlinson about “Gallows Humor in Medicine” (September-October 2011).